Deutsche Wirtschaft im Boom: Luft wird dünner - Roland Döhrn; Ferdinand Fichtner; Oliver Holtemöller; Stefan Kooths; Timo Wollmershäuser (Wirtschaftsdienst, 2018)
Die Boomphase der deutschen Wirtschaft setzt sich fort. Allerdings wird die Luft dünner: Die noch verfügbaren gesamtwirtschaftlichen Kapazitäten werden allmählich knapper, sodass die Konjunktur etwas an Schwung verliert. Dennoch bleibt das Tempo hoch: Der Aufschwung der Weltwirtschaft wird die Exporte weiter anregen; auch die Binnenwirtschaft dürfte bei der außerordentlich günstigen Lage auf dem Arbeitsmarkt schwungvoll bleiben. Zusätzlich dürfte die neue Bundesregierung durch die im Koalitionsvertrag vereinbarten fi skalischen Maßnahmen die Nachfrage stimulieren. – – The German economy continues to boom, but the air is getting thinner. Unused economic capacities are gradually shrinking, leading to a slight loss of economic impetus. The pace of economic expansion nevertheless remains brisk: the upturn in the world economy will continue to stimulate exports, and the domestic economy is also expected to remain buoyant thanks to the exceptionally favourable situation in the labour market. The fiscal measures outlined by Germany's new government in its coalition agreement can be expected to stimulate demand. Annual average economic output can be expected to rise by 2.2 % this year and by 2.0 % in 2019. This represents a 0.2 percentage point increase in the institutes' assessment of growth in gross domestic product versus their autumn 2017 forecast. Employment will continue to see clear growth, but will be weakened by labour market shortages. At the same time, gross wages can be expected to increase markedly. The inflation rate will also rise gradually from 1.7 % this year to 1.9 % in 2019.
Keywords: E32; E66; F01; 330; Wirtschaftsprognose; Wirtschaftspolitik; Internationaler Wettbewerb; Deutschland